Analisis Pengaruh Temperatur Dan Perlakuan Korosi Terhadap Ketahanan Putus Tabung Silinder Asetilin Bermaterial Drum Besi Bekas (Baja AISI 1045) - Dominggus G. H. Adoe; Wenseslaus Bunganaen; Bahrun K. A. Mandala (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2020)
corrosion rate of cylinder tube materials. The temperature variations determined by the specimen were 200ºC, 250ºC and 300ºC. The specimens were subjected to corrosion treatment with Calcium Carbide (Carbide) corrosion media, then tested. The results showed that the lowest corrosion rate was the treatment specimen, namely 48.57142 mg/cm2 day, while the specimen with the highest rate was the specimen with the provisions of 70.47619 mg/cm2 day. For the tensile test, the highest value of fracture tensile stress (σp) was the untreated specimen of 243.35 MPa, while the lowest value of fracture stress (σp) was the specimen with a temperature of 300oC of 156,786 Mpa, the highest value of fracture tensile strain (ɛp) was the specimen with 300oC of 0.166875%, while the lowest value of fracture tensile strain (ɛp) is the specimen with the provision of 250 °C of 0.12025%, the highest modulus of elasticity is the specimen with the 200oC requirement of 1569.2026 MPa, while the lowest modulus of elasticity is the specimen with 300 °C of 939.5415 MPa